2017
DOI: 10.1007/s00262-017-1968-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of VISTA correlated with immunosuppression and synergized with CD8 to predict survival in human oral squamous cell carcinoma

Abstract: V-domain Ig suppressor of T cell activation (VISTA), a novel immune checkpoint regulatory molecule, suppresses T cell mediated immune responses. The aim of the present study was to profile the immunological expression, clinical significance and correlation of VISTA in human oral squamous cell carcinoma (OSCC). Human tissue microarrays, containing 165 primary OSCCs, 48 oral epithelial dysplasias and 43 normal oral mucosae, were applied to investigate the expression levels of VISTA, CD8, cytotoxic T lymphocyte-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
131
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(138 citation statements)
references
References 39 publications
6
131
1
Order By: Relevance
“…However, and despite seeing increased CD8 T-cell function, no effect on tumor growth was detected after treatment with the combination of anti-VISTA/PD-1 treatment in an oral squamous cell carcinoma model (22). In support of our findings in human tumors, a recent study showed a positive association between VISTA and PD-L1 protein levels; and a cooperative effect of VISTA and CD8+ cells to predict survival in a retrospective cohort of human oral squamous carcinomas (31). Taken together, these data suggest that VISTA/PD-1H pathway may contribute to the adaptive resistance mechanisms operating in tumor microenvironment.…”
Section: Discussionsupporting
confidence: 89%
“…However, and despite seeing increased CD8 T-cell function, no effect on tumor growth was detected after treatment with the combination of anti-VISTA/PD-1 treatment in an oral squamous cell carcinoma model (22). In support of our findings in human tumors, a recent study showed a positive association between VISTA and PD-L1 protein levels; and a cooperative effect of VISTA and CD8+ cells to predict survival in a retrospective cohort of human oral squamous carcinomas (31). Taken together, these data suggest that VISTA/PD-1H pathway may contribute to the adaptive resistance mechanisms operating in tumor microenvironment.…”
Section: Discussionsupporting
confidence: 89%
“…In this article, we revealed that the expression of LAIR‐1 was positively related to IDO. Several studies have established that immune checkpoints, such as PD‐1 (programmed death‐1), B7‐H3 (B7 homolog 3 protein), and VISTA (V‐domain Ig suppressor of T cell activation), are drivers of immune suppression in OSCC . We also observed a significant correlation with the expression of LAIR‐1 and B7‐H3 and VISTA.…”
Section: Discussionsupporting
confidence: 65%
“…Several studies have established that immune checkpoints, such as PD-1 (programmed death-1), B7-H3 (B7 homolog 3 protein), and VISTA (V-domain Ig suppressor of T cell activation), are drivers of immune suppression in OSCC. 5,15,36,37 We also observed a significant correlation with the expression of LAIR-1 and B7-H3 and VISTA. Taken together, we suspect that LAIR-1 is likely to exert immune suppressive function in OSCC and may serve as a therapeutic target in combination with other immune checkpoints.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…48,77,86) V domain-containing Ig suppressor of T-cell activation (VISTA)BothLeads to T-cell exhaustion and T-reg recruitment in the microenvironment (87,88). …”
mentioning
confidence: 99%